2006
DOI: 10.1002/jcb.21089
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblasts and osteocytes respond differently to oscillatory and unidirectional fluid flow profiles

Abstract: Bone cells subjected to mechanical loading by fluid shear stress undergo significant architectural and biochemical changes. The models of shear stress used to analyze the effects of loading bone cells in vitro include both oscillatory and unidirectional fluid shear profiles. Although the fluid flow profile experienced by cells within bone is most likely oscillatory in nature, to date there have been few direct comparisons of how bone cells respond to these two fluid flow profiles. In this study we evaluated mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
116
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(126 citation statements)
references
References 43 publications
5
116
4
Order By: Relevance
“…MLO-Y4 cells subjected to fluid flow shear stress have shown an increase in the length of dendritic processes (Zhang et al 2006). Ponik et al (2007) have shown that MLO-Y4 osteocyte-like cells have a more dendritic morphology in response to oscillatory fluid flow. Fourty-four percent of cells have more than 3 dendrites/cell, while that is only 31% when MLO-Y4 cells held in static 258 H. Xu et al condition (Ponik et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…MLO-Y4 cells subjected to fluid flow shear stress have shown an increase in the length of dendritic processes (Zhang et al 2006). Ponik et al (2007) have shown that MLO-Y4 osteocyte-like cells have a more dendritic morphology in response to oscillatory fluid flow. Fourty-four percent of cells have more than 3 dendrites/cell, while that is only 31% when MLO-Y4 cells held in static 258 H. Xu et al condition (Ponik et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Osteoblasts and osteocytes differ in their sensitivity to FSS or stretching and demonstrate different kinetics of ␤-catenin nuclear translocation, but both cell types respond to mechanical stimulation with an increase in intracellular calcium and NO production (53)(54)(55)(56)(57). Nuclear ␤-catenin together with its binding partner Lef1 regulates genes in osteoblasts and osteocytes necessary for maintenance of normal bone mass in vivo, including cox-2, and control osteoblast as well as osteoclast differentiation and survival (27-30, 41, 58).…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of how difficult or tedious the isolation, several investigators used primary osteoblasts and osteocytes to show significant differences in markers, function, sensitivity and response to mechanical strain (89)(90)(81)(82). For example, it has been shown the primary osteoblasts are less sensitive than primary osteocytes to shear stress (39)(64) that shear stress induced less of a calcium response in a single primary osteocyte than a single primary osteoblast, (60), that shear stress induced prostaglandin production in osteocytes is inhibited by cyoskeletal disruption, but not in osteoblasts (79), different ion channels are involved in osteoblast as compared to osteocytes' response to strain (101), stress fiber organization is delayed in osteocytes compared to osteoblast-like cells in response to fluid flow (98), and osteocytes have a gene expression profile distinct from osteoblasts (45).…”
Section: Osteocytes Are Not Osteoblastsmentioning
confidence: 99%